Getting together to forget, to re-member: Mappings of care and maintenance within the independent field of dance and choreography through the participatory activities of Danish Dance Stories - Bäckman, Carolina; Deres, Andrea (Peripeti, 2024)
This article aims to unfold and contextualise a (felt) collective amnesia haunting the independent dance scene in a Danish context. By identifying potential reliefs for this condition, the authors delve into the participatory activities of the artistic initiative Danish Dance Stories, exploring and mapping out potentialities of gathering in practices of re-membering a (plural, embodied) history of dance. Taking on a wider perspective, they emphasise the need for an institutional, long-term responsibility of historicising-maintenance.